A guide to battles decisive conflicts in history - Holmes, Richard; Marix Evans, Martin (Oxford reference collection, 2018)
This book tells the stories of the most dramatic, memorable, and important conflicts in world history, from Agincourt, Lepanto, and Trafalgar, to Gettysburg, Stalingrad, and the Somme. It begins with the battle of Megiddo fought by the ancient Egyptians and takes the reader through to the Second Gulf War of 2003. On the way it encompasses almost 300 battles from around the world - from the Middle East, Asia, and Africa, to Europe and the Americas